2010
DOI: 10.1002/qj.724
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a simulated convective boundary layer over inhomogeneous vegetation

Abstract: Using a high-resolution boundary-layer model, effects of heterogeneity over a mesoscale flat domain are investigated through a series of idealised model simulations. In these simulations two different land surface types (bare soil and vegetation) are arranged in two different patterns. It is found that the effect of heterogeneity remains significant with geostrophic winds of 10 m s −1 . However, when the geostrophic wind direction is perpendicular to the alignment of the surface heterogeneities (with alignment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The incoming radiation is based on the location (latitude 2.612 • S, longitude 60.910 • W), day of year (263) and time of day. We consider cases for zero wind speed because advection influences the strength of the heterogeneity-induced circulations and can also dissipate the heterogeneity (Wang et al 2011). By maintaining clouds at the same position (no movement due to advection), length scales can be calculated without the need for advanced cloud tracking.…”
Section: Design Of Numerical Experimentsmentioning
confidence: 99%
“…The incoming radiation is based on the location (latitude 2.612 • S, longitude 60.910 • W), day of year (263) and time of day. We consider cases for zero wind speed because advection influences the strength of the heterogeneity-induced circulations and can also dissipate the heterogeneity (Wang et al 2011). By maintaining clouds at the same position (no movement due to advection), length scales can be calculated without the need for advanced cloud tracking.…”
Section: Design Of Numerical Experimentsmentioning
confidence: 99%
“…Using LES, van , Fesquet et al (2009), Wang et al (2011) and MR13 found a correlation between the local boundary-layer depth z i,local and the underlying sensible surface heat flux that produced larger values of z i,local over warmer patches and smaller values over colder patches. van attributed the varying values of z i,local in their study of idealized heterogeneities to rising SC updrafts that led to increased entrainment above the more strongly heated patches.…”
Section: Introductionmentioning
confidence: 99%
“…The local impact of a heterogeneous forcing on the structure of the interfacial layer was studied by aircraft observations (Kang et al 2007) and LES (van Heerwaarden and de Arellano 2008;Fesquet et al 2009;Wang et al 2011;Maronga and Raasch 2013). All of these studies reported a correlation between the local CBL depth z i and the underlying surface sensible heat flux, where larger values of z i were observed over stronger heated surface patches and vice versa.…”
Section: Introductionmentioning
confidence: 99%